Genetic Diversity and Trait Contribution in Rice Genotypes Using Mahalanobis D² Statistic - Rahul Kumar Maurya; Devendra Kumar Dwivedi; Sumant Pratap Singh; Nawaz Ahmad Khan; Saurabh Dixit; Adesh Kumar; Ashwini Kumar; Hemant Kumar Yadav; Shivam Kushwaha (The Bioscan, 2025)
Rice (Oryza sativa L.) is a staple food for over half of the global population, Salinity is a major abiotic stress limiting rice productivity, especially in coastal and irrigated regions. Excess salts disrupt plant metabolism, reduce water uptake, and impair growth. Rice, being salt-sensitive at seedling and reproductive stages, requires genetic improvement and adaptive strategies to ensure stable yields under saline conditions. This study, conducted during the Kharif 2024 season at the Centre of Excellence for Rice, Acharya Narendra Deva University of Agriculture and Technology, Kumarganj, Ayodhya, evaluated 121 rice genotypes along with four checks (CSR-10, CSR-36, Sarjoo-52, and MTU-7029) under saline conditions. The experimental design followed an Augmented Block Design with a spacing of 20 cm between rows and 15 cm between plants. Genetic divergence was assessed using Tocher method D² statistics across 13 yield-related traits. The analysis grouped the genotypes into nine clusters using Tocher's method, revealing significant genetic diversity. Intra-cluster distances ranged from 0.00 (Clusters III, IV, VI, IX) to 4750.90 (Cluster VIII), while the maximum inter-cluster distance was 64.863 between Clusters V and IX. Traits contributing most to genetic divergence included the total number of spikelets per panicle (48.39%), biological yield per plant (14.50%), filled spikelets per panicle (13.83%), flag leaf area (11.54%), and plant height (7.02%). These findings underscore the importance of utilizing genetically diverse parents in hybridization programs to develop high-yielding, protein-rich rice varieties, thereby addressing malnutrition and enhancing food security.